Modification and Restacking of Layered Terbium Hydroxide 2D Crystals. Issue 41 (9th November 2017) - Feng, Pingping; Shao, Baiyi; Wang, Xinying; Yang, Xiaojing
Abstract : We report that 2D crystals, prepared by delamination of layered terbium hydroxide (LTbH) intercalated with dodecyl sulfate ions (DS – ) in formamide, can be modified by DS – ions and further restacked to a new layer‐structured compound. The modification proceeds in situ in formamide through the substitution of DS – for the hydroxyl groups, which coordinate to Tb 3+ upon the delamination of the LTbH layer. With the supplementary addition of DS –, the substitution reaction progresses to a large degree of substitution, m > 2 in the chemical formula Tb2 (OH)6– m DS m · n H2 O. Since the negatively charged SO4 2– heads of DS – anchor to Tb 3+, the alkyl chains protruding outwards convert the 2D crystal from hydrophilic to hydrophobic. The modified 2D crystals aggregate in aqueous media, restacking to the layered rare‐earth compound characteristic of m greater than 2. The restacked crystals are ready to delaminate in some organic solvents owning to their structural and hydrophobic features. Abstract : Layered terbium hydroxide 2D crystals are modified into hydrophobicity by the substitution of dodecyl sulfate ions for hydroxide ions in formamide. These modified 2D crystals can be restacked to form new layered rare‐earth compounds in water. Then, they can easily be delaminated in some organic solvents.